2012
DOI: 10.4103/0974-9233.102740
|View full text |Cite
|
Sign up to set email alerts
|

Isolates and antibiotic resistance of culture-proven endophthalmitis cases presented to a referral center in Tehran

Abstract: Purpose:To evaluate the spectrum of organisms causing endophthalmitis and their resistance pattern to standard antimicrobial agents.Materials and Methods:Medical records of culture positive eyes treated at Rassoul Akram Hospital for endophthalmitis during the past 5 years were reviewed. Specimens were obtained during pars plana vitrectomy or vitreous tap.Results:Sixty-five isolates including 36 (55.4%) gram-positive organisms, 28 gram-negative organisms (43.1%), and 1 (1.5%) fungus were studied. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Another study by Sharma et al reported 4/11 GNB isolated from patients with endophthalmitis are resistant to ceftazidime [10]. Study from Tehran by Falavarjani et al has reported low resistance of ceftazidime (10 %) in GNB [11]. Schimel et al from USA reviewed the spectrum and susceptibilities of isolates from patients with endophthalmitis and found all GNB (100 %) susceptible to ceftazidime [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study by Sharma et al reported 4/11 GNB isolated from patients with endophthalmitis are resistant to ceftazidime [10]. Study from Tehran by Falavarjani et al has reported low resistance of ceftazidime (10 %) in GNB [11]. Schimel et al from USA reviewed the spectrum and susceptibilities of isolates from patients with endophthalmitis and found all GNB (100 %) susceptible to ceftazidime [9].…”
Section: Discussionmentioning
confidence: 95%
“…The spectrum and antibiotic susceptibility of organisms isolated from patients with endophthalmitis vary by region and country. Several reports have shown that all the Gram positive bacterial isolates are susceptible to vancomycin [8][9][10][11] except few cases of endophthalmitis with vancomycin resistant Enterococcus species [12,13]. Khera et al from Hyderabad, India have shown that 1.5 % of the total Gram positive isolates are resistant to vancomycin [14].…”
Section: Discussionmentioning
confidence: 99%
“…[ In their investigation the most common organism was Coagulasenegative staphylococcus [27]. In another study which was conducted in 2012, Staphylococcus, Streptococcus, Bacillus cereus and Pseudomonas aeruginosa were detected in Iranian endophthalmitis specimens [28].…”
Section: Discussionmentioning
confidence: 99%
“…Somani et al 31 (Canada), Pei-Chang et al 32 (Taiwan), and Falavarjani et al 33 (Iran) reported that cataract surgery was the most common predisposing surgical procedure in postoperative endophthalmitis patients. Since cataract surgery is the most common intraocular surgery, most cases of post-operative endophthalmitis occur after cataract extraction.…”
Section: Discussionmentioning
confidence: 99%